(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Office of Safety and Security has a lot of problems in preserving its data, particularly in monitoring reports, certificates, and passes and inspecting infrastructures. The staff needs to submit a narrative report to the OIC and scan each paper carefully. It takes a lot of time, efforts and it affects the productivity of the department, especially the problem of pilling a request item; then OIC needs to go back and forth to submit and follow up on the progress of the request to different campuses of the Bestlink College of the Philippines. In reality, speaking it takes a lot of budget for the department’s operation cost. As a result, the developers successfully created a system that met all the client requirements that you can see in the project’s deliverables and product backlog. As you can see, Appendix F shows how the client navigated the system and gave the system a 90% completion rate. They wanted the system to be implemented in their department. The system helps the Office of Safety and Security monitor, report, make and release passes, and request items without going out into their workplace. Lastly, the safety officers can easily track and inspect the facility by simply inputting information into the mobile application and web management system. I have a deep understanding of the study and complied with all the requirements needed. The developers successfully implemented and migrated the data to the new system approach. The modules and submodules are successfully working by inputting data into mobile applications that will appear or see the output to the web-based system. Also, the web has an input feature like mobile so that the personnel can navigate the system through the web.